Optical laminate and smart window including same

By optimizing the peeling force of the surface protective film and the hardness of the hard coat, the surface damage and bubble problems of the optical laminate during the production process are solved, and higher durability and stability are achieved.

CN119487441APending Publication Date: 2025-02-18DONGWOO FINE CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380051712.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-05-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing optical laminates with variable transmittance are prone to surface damage or scratches during production or transportation, resulting in reduced optical characteristics, and insufficient or excessive peeling force of the surface protective film, resulting in bubbles during ITO evaporation. question.

Method used

The peeling force of the surface protective film is 1.0N/25mm to 2.4N/25mm, and the hardness of the hard coating layer is HB to 6H on one or both sides of the optical laminate to protect the dimming laminate from the outside. Impact and post-process influence.

Benefits of technology

It effectively prevents damage to the frame sealing glue and bubbles from entering the liquid crystal, improves the durability of the optical laminate, and prevents bubbles from entering when the transparent conductive layer is vacuum evaporated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487441A_ABST
    Figure CN119487441A_ABST
Patent Text Reader

Abstract

The present invention relates to a variable transmittance optical laminate and a smart window comprising the same, the variable transmittance optical laminate comprising a dimming laminate, the dimming laminate comprising: a first polarizing plate; a first transparent conductive layer formed on one surface of the first polarizing plate; a second polarizing plate facing the first polarizing plate; a second transparent conductive layer formed on one surface of the second polarizing plate and facing the first transparent conductive layer; and a liquid crystal layer which is provided between the first transparent conductive layer and the second transparent conductive layer, and which is provided with a surface protective film and / or a hard coat layer on one or both surfaces of the light-dimming laminate. At least one of the first transparent conductive layer and the second transparent conductive layer is formed so as to be in direct contact with one of the first polarizing plate and the second polarizing plate, the release force of the surface protective film is 1.0 N / 25 mm to 2.4 N / 25 mm, and the surface pencil hardness of the hard coat layer is HB to 6H.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical stack and a smart window comprising the same. Background Art

[0002] Generally speaking, glass windows of mobile tools such as vehicles are often coated with external light blocking coatings. However, the transmittance of glass windows of conventional mobile tools is fixed, and the transmittance of external light blocking coatings is also fixed. Therefore, since the overall transmittance of the windows of such conventional mobile tools is fixed, accidents may occur. For example, if the overall transmittance is set low, there will be no problem during the day when the surrounding light is sufficient. However, in situations such as the night when the surrounding light is insufficient, there is a problem that it is difficult for the driver and the like to correctly view the surrounding conditions of the mobile tool. In addition, if the overall transmittance is set high, there is a problem that it may cause dazzle to the driver and the like during the day when the surrounding light is sufficient. For this reason, a variable transmittance optical laminate that can change the transmittance of light when a voltage is applied has been developed.

[0003] On the other hand, if one wishes to use such a variable transmittance optical layered body to manufacture a smart window, the optical layered body is generally manufactured and then glass is bonded to one or both surfaces of the optical layered body.

[0004] However, before the optical laminate is bonded to glass, that is, during the process of manufacturing or conveying the optical laminate, if the optical laminate has surface damage or scratches, the optical properties of the optical laminate may be degraded.

[0005] Therefore, it is necessary to protect the optical stack from surface damage or scratches that may occur during the handling of the optical stack itself used in the production of smart windows.

[0006] For this purpose, a surface protection film that can be attached to one or both surfaces of the optical laminate to protect the optical laminate from surface damage or scratches is used. For example, Korean Patent Publication No. 10-2001-0101097 also discloses a surface protection film.

[0007] However, for such a surface protective film, if the peeling force relative to the attachment surface is insufficient, there is a problem of bubbles appearing at the interface between the surface protective film and the attachment surface during the vapor deposition process of ITO, etc. If the peeling force relative to the attachment surface is too large, there is a problem of the internal film of the laminate being peeled off or bubbles entering the liquid crystal during the peeling process.

[0008] The above-mentioned Korean Patent Publication No. 10-2001-0101097 also has a problem that bubbles appear at the interface between the surface protection film and the attachment surface during the ITO evaporation process because the peeling force is insufficient for use in the production process of the optical laminate for smart windows.

[0009] Therefore, there is an increasing demand for optical laminates having a surface protection film capable of protecting the optical laminate without causing these problems. Summary of the invention

[0010] Technical issues

[0011] An object of the present invention is to provide a variable transmittance optical stack that can protect the light-adjusting stack from external impacts, scratches, etc. and prevent damage to the light-adjusting stack that may occur during the process.

[0012] Solution to the problem

[0013] In order to achieve the above-mentioned purpose, the present invention provides a variable transmittance optical stack, which includes a dimming stack, and the dimming stack includes: a first polarizing plate; a first transparent conductive layer, which is formed on one side of the above-mentioned first polarizing plate; a second polarizing plate, which is opposite to the above-mentioned first polarizing plate; a second transparent conductive layer, which is formed on one side of the above-mentioned second polarizing plate and opposite to the above-mentioned first transparent conductive layer; and a liquid crystal layer, which is arranged between the above-mentioned first transparent conductive layer and the second transparent conductive layer, wherein at least one of a surface protection film and a hard coating layer is provided on one side or both sides of the above-mentioned dimming stack, at least one of the above-mentioned first transparent conductive layer and the second transparent conductive layer is formed to directly contact one of the above-mentioned first polarizing plate and the second polarizing plate, the peeling force of the above-mentioned surface protection film is 1.0N / 25mm~2.4N / 25mm, and the surface pencil hardness of the above-mentioned hard coating layer is HB~6H.

[0014] Effects of the Invention

[0015] According to an embodiment of the optical laminate of the present invention, since the peeling force of the surface protection film is optimized, it is possible to prevent the sealant from being damaged and bubbles from entering the liquid crystal when the surface protection film is peeled off.

[0016] In addition, according to the optical laminated body of one embodiment of the present invention, since the peeling force of the surface protection film is optimized, it is possible to prevent bubbles from entering between the light-adjusting laminated body and the surface protection film during vacuum deposition of the transparent conductive layer.

[0017] In addition, according to another embodiment of the optical laminate of the present invention, since the surface pencil hardness of the hard coating layer is optimized, even if the optical laminate is not provided with a surface protection film, the surface of one or both sides of the dimming laminate can be protected from the influence of subsequent processes and the external environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 1 is a diagram showing a stacked structure of a light control stack according to an embodiment of the present invention.

[0019] Figure 2a to Figure 2e 1 is a diagram showing a stacked structure of polarizing plates according to one or more embodiments of the present invention.

[0020] Figure 3 and 4 1 is a diagram showing a stacked structure of a variable transmittance optical stack according to one or more embodiments of the present invention.

[0021] Figure 5a to Figure 5c and Figure 6a to Figure 6c is a diagram showing a stacked structure of a smart window according to one or more embodiments of the present invention.

[0022] The meanings of the symbols in the above figure are as follows:

[0023] 100: Dimming stack

[0024] 200: Polarizing plate

[0025] 210: Polarizer

[0026] 220: Protective layer

[0027] 230: Phase difference adjustment layer

[0028] 240: Refractive index adjustment layer

[0029] 300: Transparent conductive layer

[0030] 400: Liquid crystal layer

[0031] 500: Oriented film

[0032] 600: Frame Sealing Adhesive

[0033] 700: Surface protection film

[0034] 800: Hard coating

[0035] 910: Glass for vehicles

[0036] 920: Glass for windows DETAILED DESCRIPTION

[0037] The present invention relates to a variable transmittance optical stack, which optimizes the peeling force of a surface protective film to prevent the frame sealant from being damaged and bubbles from entering the liquid crystal when the surface protective film is peeled off, and to prevent bubbles from entering between the dimming stack and the surface protective film when a transparent conductive layer is vacuum evaporated.

[0038] The present invention also relates to a variable transmittance optical laminate that optimizes the surface pencil hardness of a hard coat layer so that even without a surface protective film, one or both surfaces of the optical laminate can be protected from subsequent processes and external environment.

[0039] In more detail, it relates to a variable transmittance optical stack, which includes a dimming stack, wherein the dimming stack includes: a first polarizing plate; a first transparent conductive layer formed on one side of the first polarizing plate; a second polarizing plate opposite to the first polarizing plate; a second transparent conductive layer formed on one side of the second polarizing plate and opposite to the first transparent conductive layer; and a liquid crystal layer arranged between the first transparent conductive layer and the second transparent conductive layer, wherein at least one of a surface protective film and a hard coating layer is provided on one side or both sides of the dimming stack, at least one of the first transparent conductive layer and the second transparent conductive layer is formed to directly contact one of the first polarizing plate and the second polarizing plate, the peeling force of the surface protective film is 1.0N / 25mm~2.4N / 25mm, and the surface pencil hardness of the hard coating layer is HB~6H.

[0040] The variable transmittance optical laminate of the present invention is particularly suitable for the technical field in which the transmittance of light can be changed by application of voltage, and can be used, for example, in smart windows and the like.

[0041] The so-called smart window refers to an optical structure that changes the transmittance of light according to the application of an electrical signal to control the amount of light or heat passing through. In other words, a smart window can change to a transparent, opaque or semi-transparent state according to voltage, and is also called variable transmittance glass, dimming glass or smart glass.

[0042] Smart windows can be used as partitions for dividing the interior space of vehicles and buildings or as partitions for privacy protection, or as skylights arranged in the openings of buildings. They can also be used as highway signs, billboards, scoreboards, clocks or advertising screens, and can replace the glass of transportation vehicles such as windows or skylights such as cars, buses, airplanes, ships or trains.

[0043] The variable transmittance optical laminate of the present invention can also be used as a smart window in the above technical fields, but because the conductive layer is directly formed on the polarizing plate and does not include a separate substrate for forming the conductive layer, the thickness is thin and is conducive to bending properties, and it can be particularly suitable for use in smart windows for vehicles or buildings. In one or more embodiments, the smart window using the variable transmittance optical laminate of the present invention can be used in transportation tools, such as the front window, rear window, side window and skylight of a car, or a building window, etc. In addition to the use of blocking external light, it can also be used for internal space division or privacy protection of cars or buildings, such as internal partitions, and can also be used in wearable devices such as helmets, glasses or watches.

[0044] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the accompanying drawings. However, the following drawings attached to this specification are only examples of preferred embodiments of the present invention, which serve to further understand the above-mentioned invention content and the technical concept of the present invention, so the present invention should not be interpreted only in accordance with the matters recorded in these drawings.

[0045] The terms used in this specification are intended to illustrate the embodiments and are not intended to limit the present invention. In this specification, unless otherwise specified in the context, the singular form also includes the plural form. For example, the "polarizing plate" used in this specification may refer to at least one of the first polarizing plate and the second polarizing plate, and the "transparent conductive layer" may refer to at least one of the first transparent conductive layer and the second transparent conductive layer.

[0046] The terms "comprises" and / or "comprising" used in this specification are used to mean that they do not exclude the existence or addition of one or more other constituent elements, steps, operations and / or elements other than the mentioned constituent elements, steps, operations and / or elements. Throughout the specification, the same reference numerals refer to the same constituent elements.

[0047] As illustrated in the accompanying drawings, spatially relative terms "below", "bottom", "lower", "above", "upper surface", "upper part", etc. can be used to easily describe the correlation between one element or constituent element and other elements or constituent elements. Spatially relative terms should be understood as terms that include different directions of the elements when in use or in operation in addition to the directions illustrated in the drawings. For example, when the elements illustrated in the drawings are turned over, the elements described as "below" or "lower" of other elements can be placed "above" other elements. Therefore, the exemplary term "below" can include both directions below and above. Elements can also be oriented in other directions, so spatially relative terms can be interpreted according to orientation.

[0048] The “top-view direction” used in the present specification may be interpreted as a direction perpendicular to the polarizing plate and / or the transparent conductive layer, that is, a direction viewed from the visible side of a user.

[0049] Figure 1 FIG. 2 is a diagram showing a stacked structure of a light-adjusting stack according to one embodiment of the present invention, and FIG. 3 is a diagram showing a stacked structure of a polarizing plate according to one or more embodiments of the present invention. Figure 3 and 4 5 and 6 are diagrams showing the stacking structure of a smart window according to one or more embodiments of the present invention.

[0050] Reference Figure 1 The dimming stack 100 according to an embodiment of the present invention may include a first polarizing plate 200 - 1 , a second polarizing plate 200 - 2 , a first transparent conductive layer 300 - 1 , a second transparent conductive layer 300 - 2 , and a liquid crystal layer 400 .

[0051] 2, the polarizing plate 200 may include a polarizer 210, and may further include functional layers such as a protective layer 220, a phase difference adjustment layer 230, and a refractive index adjustment layer 240 on one or both sides of the polarizer 210. For example, the polarizing plate 200 may include a polarizer 210 and a protective layer 220 stacked on one or both sides of the polarizer 210 (see Figure 2a and Figure 2b ), which may include a polarizer 210, a protective layer 220 laminated on one surface of the polarizer 210, and a phase difference adjustment layer 230 laminated on the other surface of the polarizer 210 opposite to the one surface (see Figure 2c ), which may include a polarizer 210, a protective layer 220 stacked on one side of the polarizer, and a phase difference adjustment layer 230 and a refractive index adjustment layer 240 stacked in sequence on the other side of the polarizer 210 opposite to the one side (see Figure 2d ), which may include a polarizer 210, a protective layer 220 stacked on one side of the polarizer, and a protective layer 220 and a phase difference adjustment layer 230 stacked in sequence on the other side of the polarizer 210 opposite to the one side (see Figure 2e ).

[0052] The polarizer 210 may be a polarizer that is previously available or developed in the future. For example, a stretched polarizer or a coating polarizer may be used.

[0053] In one embodiment, the stretched polarizer may include a stretched polyvinyl alcohol (PVA) resin. The polyvinyl alcohol (PVA) resin may be a polyvinyl alcohol resin obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith may also be mentioned. As the other monomers mentioned above, unsaturated carboxylic acid series, unsaturated sulfonic acid series, olefin series, vinyl ether series, acrylamide series monomers having an ammonium group, etc. may be mentioned. In addition, the polyvinyl alcohol (PVA) resin includes modified substances, for example, polyvinyl formal or polyvinyl acetal modified by aldehydes may also be mentioned.

[0054] In one embodiment, the coating type polarizer may be formed by using a liquid crystal coating composition. In this case, the liquid crystal coating composition may include a reactive liquid crystal compound and a dichroic dye.

[0055] The reactive liquid crystal compound may refer to a compound containing a mesogen skeleton and one or more polymerizable functional groups. Such reactive liquid crystal compounds are widely known by the name of so-called reactive mesogens (RM). The reactive liquid crystal compound may be polymerized by light or heat to form a cured film having a polymer network while maintaining the liquid crystal arrangement.

[0056] The reactive liquid crystal compound may be a monofunctional or polyfunctional reactive liquid crystal compound. The monofunctional reactive liquid crystal compound may be a compound having one polymerizable functional group, and the polyfunctional reactive liquid crystal compound may be a compound having two or more polymerizable functional groups.

[0057] The above-mentioned dichroic dye is a component added to the liquid crystal coating composition to impart polarization characteristics, and has a property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction. The above-mentioned dichroic dye can use a dichroic dye developed in the past or in the future, for example, it can include one or more selected from the group consisting of azo dyes (azo dyes), anthraquinone dyes (anthraquinone dyes), perylene dyes (perylene dyes), merocyanine dyes (merocyanine dyes), azomethine dyes (azomethine dyes), phthaloperylene dyes (phthaloperylene dyes), indigo dyes (indigodyes), dioxadine dyes (dioxadine dyes), polythiophene dyes (polythiophene dyes) and phenoxazine dyes (phenoxazine dyes).

[0058] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, for example, propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, and chloroform, etc. In addition, the liquid crystal coating composition may further include a leveling agent, a polymerization initiator, etc., within the range that does not hinder the polarization characteristics of the coating film.

[0059] The protective layer 220 is intended to protect the polarization characteristics of the polarizer 210 from being affected by subsequent processes and the external environment, and can be implemented in the form of a protective film or the like.

[0060] like Figure 2a and Figure 2b As shown in the figure, the protective layer 220 may be formed directly in contact with one or both surfaces of the polarizer 210, but is not limited thereto. For example, the protective layer may be used as a multilayer structure in which more than one protective layer is continuously stacked, and may be formed in direct contact with other functional layers.

[0061] In one or more embodiments, the protective layer 220 may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose, triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA) and cyclic olefin polymer (COP).

[0062] like Figure 2c and Figure 2d As shown in the figure, the phase difference adjustment layer 230 can be formed in direct contact with one surface of the polarizer 210, but is not limited thereto. Figure 2e As shown in the figure, the phase difference adjustment layer 230 may be formed on one surface of the protective layer 220 so that the polarizer 210 , the protective layer 220 , and the phase difference adjustment layer 230 are stacked in sequence.

[0063] The phase difference adjustment layer 230 may be a stretched polymer film or a liquid crystal polymer film obtained by appropriately stretching a polymer film capable of imparting optical anisotropy.

[0064] In one embodiment, the above-mentioned polymer stretch film can use a polymer layer containing the following substances: polyolefins such as polyethylene (PE) or polypropylene (PP), cyclo olefin polymers (COP: cyclo olefin polymer) such as polynorbornene, polyvinyl chloride (PVC), polyacrylonitrile (PAN), polysulfone (PSU), acrylic resin (acryl resin), polycarbonate (PC), polyesters such as polyethyleneterephthalate (PET), polyacrylate, polyvinyl alcohol (PVA) or triacetyl cellulose (TAC) and other cellulose ester polymers, or copolymers of two or more monomers among the monomers forming the above-mentioned polymers, etc.

[0065] The method for obtaining the above-mentioned polymer stretch film is not particularly limited, for example, it can be obtained by stretching the above-mentioned polymer material after being molded into a film shape. The above-mentioned method of being molded into a film shape is not particularly limited, and can be molded into a film by known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, extrusion molding, foam molding, and tape casting, or by secondary processing molding methods such as compression molding and vacuum molding. Among them, extrusion molding and tape casting are preferably used. At this time, for example, an extruder equipped with a T-shaped mold, a circular mold, etc. can be used to extrusion mold the unstretched film. In the case of obtaining a molded product by extrusion molding, a material that has been melt-mixed in advance with various resin components, additives, etc. can be used, and it is also possible to mold via melt mixing during extrusion molding. In addition, a solvent shared by various resin components can also be used, such as chloroform, dichloromethane, etc. After the various resin components are dissolved, tape casting, drying and solidification are performed, thereby the unstretched film is tape cast.

[0066] For the above-mentioned polymer stretched film, the above-mentioned formed film can be uniaxially stretched along the machine flow direction (MD; Mechanical Direction, longitudinal or length direction) and uniaxially stretched along the direction perpendicular to the machine flow direction (TD; Transverse Direction, transverse or width direction). In addition, the biaxially stretched film can also be manufactured by stretching by a sequential biaxial stretching method of roller stretching and tenter stretching, a simultaneous biaxial stretching method based on tenter stretching, a biaxial stretching method based on tubular stretching, etc.

[0067] The liquid crystal polymer film may include a reactive liquid crystal compound in a polymerized state. The reactive liquid crystal compound may be similarly applied to the reactive liquid crystal compound of the coating type polarizer.

[0068] In one or more embodiments, the thickness of the phase difference adjustment layer 230 may be 10 μm to 100 μm in the case of a polymer stretched film, and may be 0.1 μm to 5 μm in the case of a liquid crystal polymer film.

[0069] The refractive index adjustment layer 240 is provided to compensate for the refractive index difference of the optical laminate caused by the transparent conductive layer 300, and can play a role in improving the visible characteristics by reducing the refractive index difference. In addition, the refractive index adjustment layer 240 can also be provided to correct the color caused by the transparent conductive layer 300. On the other hand, in the case where the transparent conductive layer has a pattern, the refractive index adjustment layer 240 can compensate for the transmittance difference between the pattern area where the pattern is formed and the non-pattern area where the pattern is not formed.

[0070] Specifically, the transparent conductive layer 300 is stacked adjacent to other components (e.g., polarizers, etc.) having a different refractive index from the transparent conductive layer 300. Due to the difference in refractive index with other adjacent layers, a difference in light transmittance may be induced. In particular, when the transparent conductive layer is patterned, the patterned area and the non-patterned area may appear different. Therefore, by including the refractive index adjustment layer 240, the refractive index can be compensated to reduce the difference in light transmittance of the optical laminate. In particular, when the transparent conductive layer is patterned, the patterned area and the non-patterned area will not appear different.

[0071] In one embodiment, the refractive index of the refractive index adjustment layer 240 can be appropriately selected according to the materials of other adjacent components, preferably 1.4 to 2.6, more preferably 1.4 to 2.4. In this case, light loss caused by a significant refractive index difference between other components such as the polarizer 210 and the transparent conductive layer 300 can be prevented.

[0072] The above-mentioned refractive index adjustment layer 240 is not particularly limited as long as it can prevent a significant refractive index difference between other components such as the polarizer 210 and the transparent conductive layer 300. Compounds for forming a refractive index adjustment layer that have been previously or developed in the future can be used. For example, it can be formed by a refractive index adjustment layer forming composition containing a polymerizable isocyanurate compound.

[0073] In one embodiment, in addition to the above functional layers, the polarizing plate 200 may further include other functional layers to assist or enhance the characteristics of the polarizer. For example, in order to further improve the mechanical durability, an overcoat or a hard coating layer may also be included.

[0074] In one or more embodiments, the polarizing plate 200 may have a thickness of 30 μm to 200 μm, preferably 30 μm to 170 μm, and more preferably 50 μm to 150 μm. In this case, a thin optical laminate can be manufactured while maintaining the optical properties of the polarizing plate 200 .

[0075] The transparent conductive layer 300 is provided for driving the liquid crystal layer 400 and can be formed in direct contact with the polarizing plate 200. Figure 1 As shown in the figure, the first transparent conductive layer 300 - 1 and the second transparent conductive layer 300 - 2 may be formed in direct contact with the first polarizing plate 200 - 1 and the second polarizing plate 200 - 2 , respectively.

[0076] In the past, a dimming laminate used to manufacture smart windows and the like was manufactured by forming a conductive layer for liquid crystal driving on one side of a substrate and bonding the other side of the substrate to a polarizing plate. However, the dimming laminate 100 of the present invention is characterized in that a conductive layer is directly formed on one side of a polarizing plate without including a separate substrate for forming the conductive layer, thereby reducing the thickness of the laminate and improving the transmittance and bending characteristics in a light transmission mode.

[0077] In one embodiment, the transparent conductive layer 300 may be formed by direct evaporation on one side of the polarizing plate 200. In this case, in order to improve the adhesion between the transparent conductive layer 300 and the polarizing plate 200, the transparent conductive layer 300 may be formed by direct contact with the pre-treated side of the polarizing plate 200 after pre-treatment such as corona treatment or plasma treatment is performed on one side of the polarizing plate 200. The pre-treatment is not limited to corona treatment or plasma treatment, and a pre-treatment process developed in the past or in the future may be used within the scope that does not impair the purpose of the present invention.

[0078] In another embodiment, in order to improve the adhesion between the transparent conductive layer 300 and the polarizing plate 200 , an easy-adhesion layer (not shown) disposed on one side of the polarizing plate 200 may be placed between them so as to be in direct contact with the polarizing plate 200 .

[0079] The above-mentioned transparent conductive layer 300 preferably has a transmittance of 50% or more with respect to visible light. For example, it may include one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based substances, conductive polymers, conductive inks and nanowires, but is not limited to this, and materials for transparent conductive layers developed in the past or in the future may be used.

[0080] In one or more embodiments, the transparent conductive oxide may include one or more selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), indium tin zinc oxide (IZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), fluorine tin oxide (FTO), and zinc oxide (ZnO). In addition, the metal may include one or more selected from the group consisting of gold (Au), silver (Ag), copper (Cu), aluminum (Al), platinum (Pt), palladium (Pd), chromium (Cr), titanium (Ti), tungsten (W), niobium (Nb), tantalum (Ta), vanadium (V), iron (Fe), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), and alloys containing at least one of them, for example, may include silver-palladium-copper (APC) alloy or copper-calcium (CuCa) alloy. The carbon-based material may include one or more selected from the group consisting of carbon nanotubes (CNT) and graphene, and the conductive polymer may include one or more selected from the group consisting of polypyrrole, polythiophene, polyacetylene, poly(3,4-ethylenedioxythiophene) (PEDOT) and polyaniline, etc. The conductive ink may be an ink mixed with metal powder and a curable polymer binder, and the nanowire may be, for example, silver nanowire (AgNW).

[0081] In addition, the transparent conductive layer 300 may be formed of a two-layer structure or more by combining the above-mentioned materials. For example, in order to reduce the reflectivity of incident light and increase the transmittance, the transparent conductive layer 300 may be formed of a two-layer structure including a metal layer and a transparent conductive oxide layer.

[0082] The liquid crystal layer 400 may adjust the transmittance of light incident from one or more directions according to an electric field, thereby changing a driving mode of the optical stack.

[0083] The liquid crystal layer 400 may include a liquid crystal compound and a spacer, for example, Figure 1 As shown in the figure, it may refer to a region defined by the first alignment film 500 - 1 , the second alignment film 500 - 2 , and the sealant 600 .

[0084] The liquid crystal compound is not particularly limited as long as it can be driven by an electric field and can control light transmittance, and any liquid crystal compound developed in the past or in the future can be used. For example, the contents regarding the reactive liquid crystal compound of the coatable polarizer can be similarly applied.

[0085] The liquid crystal behavior of the liquid crystal layer 400 is not particularly limited. Figure 1 As shown in the figure, it can be driven by a twisted nematic (TN) mode. In addition, it can also be driven by a supertwisted nematic (STN) mode, a vertical alignment (VA) mode, an electrically controlled birefringence (ECB) mode, etc.

[0086] The spacer may include at least one of a ball spacer and a column spacer, and a ball spacer is particularly preferred. There may be more than one spacer, and the height is preferably 1 μm to 10 μm. In addition, when viewed from a top view, the area occupied by the spacer in the liquid crystal layer 400 is preferably 0.01 to 10% relative to the area of ​​the liquid crystal layer 400 in order to improve the visibility of the user and the transmittance in the light transmission mode.

[0087] In one embodiment, the liquid crystal layer 400 may further include an alignment film 500 as needed, for example, the alignment film 500 may be formed on both sides of the liquid crystal layer 400 including the liquid crystal compound.

[0088] The alignment film 500 is not particularly limited as long as it is used to impart alignment to the liquid crystal compound, and may preferably include a photo-alignment or photo-curable polymer, etc. For example, the alignment film 500 may be prepared by coating an alignment film coating composition including a photo-alignment or photo-curable polymer, a photopolymerization initiator, and a solvent, and curing the coating composition.

[0089] The photo-orientable or photo-curable polymer is not particularly limited, and cinnamate polymers, polyimide polymers, and the like can be used. For example, polyvinyl cinnamate (PVCi), polysiloxane cinnamate (PSCN), poly(ω(4-chalconyloxy)alkoxyphenyl maleimide), 6-FDA-HAB-Cl, and the like can be used. Polymers that can show orientation and are developed in the past or in the future can be used.

[0090] The frame sealant 600 is located between the first polarizing plate 200-1 and the second polarizing plate 200-2 in the non-active area, and plays the role of combining the first polarizing plate and the second polarizing plate. It can be arranged between the first polarizing plate 200-1 and the second polarizing plate 200-2 together with the spacer to ensure that space is provided for the liquid crystal layer 400.

[0091] The frame sealant 600 may include a curable resin as a base resin. As the base resin, a UV curable resin or a thermosetting resin known in the art as being usable for frame sealant may be used. The UV curable resin may be a polymer of a UV curable monomer. The thermosetting resin may be a polymer of a thermosetting monomer.

[0092] As the base resin of the above-mentioned frame sealant 600, for example, an acrylate resin, an epoxy resin, a urethane resin, a phenol resin or a mixture of the above-mentioned resins can be used. In one embodiment, the above-mentioned base resin can be an acrylate resin, and the above-mentioned acrylate resin can be a polymer of an acrylic monomer. The above-mentioned acrylic monomer can be, for example, a multifunctional acrylate. In another embodiment, the above-mentioned frame sealant can also contain a monomer component in the base resin. The above-mentioned monomer component can be, for example, a monofunctional acrylate. In this specification, a monofunctional acrylate can refer to a compound having one acryloyl group, and a multifunctional acrylate can refer to a compound having more than two acryloyl groups. The above-mentioned curable resin can be cured by irradiation with ultraviolet rays and / or heating. Regarding the above-mentioned ultraviolet irradiation conditions or heating conditions, they can be appropriately implemented within the scope that does not damage the purpose of the present application. The above-mentioned frame sealant can also contain an initiator, such as a photoinitiator or a thermal initiator, as needed.

[0093] The frame sealant 600 may be formed by a method commonly used in the art, for example, by using a dispensing machine with a nozzle to apply the frame sealant to the periphery of the liquid crystal layer (ie, the inactive area).

[0094] Reference Figure 3 A variable transmittance optical stack according to an embodiment of the present invention may include a light-adjusting stack 100 and surface protection films 700 formed on both surfaces of the light-adjusting stack.

[0095] The surface protection film 700 may be provided to prevent surface scratches, contamination, corrosion, etc. that may occur during the manufacture, transportation or storage of the dimming stack 100, and may be peeled off and removed from the dimming stack before glass such as vehicle glass 910 or building glass 920 is attached to the dimming stack 100 (refer to FIG. 5 ).

[0096] The peeling force of the surface protection film 700 relative to the dimming stack is preferably 1.0N / 25mm to 2.4N / 25mm. The peeling force can be obtained by measuring the 180° peeling force (N / 25mm) between the dimming stack 100 and the surface protection film at a speed of 300mm / min using a universal testing machine. If the peeling force of the surface protection film satisfies the above range, bubbles will not enter the optical stack and will not damage the frame sealant when manufacturing the dimming stack 100 or when peeling the surface protection film 700, thereby further improving the durability of the optical stack.

[0097] The surface protection film 700 may include a base film and an adhesive layer formed on the base film.

[0098] The substrate film may be a substrate film developed in the past or in the future, for example, it may include one or more selected from the group consisting of polyolefin films, polyester films, acrylic films, styrene films, amide films, polyvinyl chloride films, polyvinylidene chloride films and polycarbonate films. Considering the possibility of deformation during the manufacture, transportation or storage of the dimming stack 100, the adhesion to the dimming stack 100, etc., the thickness of the substrate film may be 10 μm to 300 μm.

[0099] The adhesive layer may be formed using an adhesive, and preferably has appropriate adhesive strength so that when peeling off the surface protection film 700 , only the surface protection film 700 can be cleanly removed from the dimming stack 100 without affecting other components such as the frame sealant, while having transparency and thermal stability.

[0100] The adhesive may be an adhesive developed in the past or in the future, and in one or more embodiments, may be an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyvinyl alcohol adhesive, a polyvinyl pyrrolidone adhesive, a polyacrylamide adhesive, a cellulose adhesive, a vinyl alkyl ether adhesive, etc. The adhesive is not particularly limited as long as it has adhesive force and viscoelasticity. From the perspective of ease of acquisition, it is preferably an acrylic adhesive, for example, it may contain a (meth)acrylate copolymer, a crosslinking agent, a solvent, etc.

[0101] The crosslinking agent may be any crosslinking agent developed in the past or in the future, and may include, for example, polyisocyanate compounds, epoxy resins, melamine resins, urea resins, dialdehydes, methylol polymers, and preferably polyisocyanate compounds.

[0102] The above-mentioned solvent may include a common solvent used in the field of resin compositions, for example, alcohol compounds such as methanol, ethanol, isopropanol, butanol, propylene glycol methoxy alcohol, ketone compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, acetate compounds such as methyl acetate, ethyl acetate, butyl acetate, propylene glycol methoxy acetate, cellosolve compounds such as methyl cellosolve, ethyl cellosolve, propyl cellosolve, hydrocarbon compounds such as hexane, heptane, benzene, toluene, xylene, etc. Solvents such as these can be used. These solvents can be used alone or in combination of two or more.

[0103] The thickness of the adhesive layer can be appropriately determined according to the type of resin that functions as an adhesive, adhesive strength, the environment in which the adhesive is used, etc. In one embodiment, the adhesive layer can have a thickness of 1 μm to 30 μm so that the peeling force of the surface protection film 700 is 1.0 N / 25 mm to 2.4 N / 25 mm.

[0104] Reference Figure 4 A variable transmittance optical stack according to another embodiment of the present invention may include a light-adjusting stack 100 and a hard coating layer 800 formed on both surfaces of the light-adjusting stack.

[0105] The hard coating layer 800 may be provided to protect components such as the polarizing plate, the variable transmittance layer, and the dimming stack from external physical and chemical impacts. In terms of protecting the dimming stack 100 from the external environment, it may substantially perform the same function as the surface protection layer 700. Therefore, when the variable transmittance optical stack of the present invention includes the hard coating layer 800, the surface protection film 700 may not be included (see Figure 4 and 6).

[0106] The surface pencil hardness of the hard coating layer 800 is preferably HB to 6H to protect the dimming stack 100 from the external environment. The surface pencil hardness can be measured by applying a 500g load using a pencil hardness tester (Pencil Hardness Tester, Sukbo Science Co., Ltd., South Korea). The pencil can be a Mitsubishi product. Each pencil hardness is measured 5 times and evaluated based on whether scratches are confirmed by the naked eye after heat treatment at 100°C for 10 minutes. When the surface pencil hardness of the hard coating layer meets the above range, the hard coating layer can have excellent wear resistance and can prevent surface defects in subsequent processes.

[0107] The hard coating layer 800 may be a hard coating layer developed in the past or in the future, and according to one embodiment of the present invention, may be formed of a hard coating composition including an acrylate or epoxy compound, inorganic particles, a photoinitiator, etc. The acrylate compound may include a monomer or oligomer containing a (meth)acrylate group, and the term "(meth)acryloyl-" used in this specification may be used to refer to "methacryloyl-", "acryloyl-", or both. Non-limiting examples of the acrylate compounds include neopentyl glycol acrylate, 1,6-hexanediol (meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and the like. (Meth) acrylate, dipentaerythritol penta (meth) acrylate, dipentaerythritol tetra (meth) acrylate, dipentaerythritol hexa (meth) acrylate, tripentaerythritol tri (meth) acrylate, tripentaerythritol hexa (meth) acrylate, bis (2-hydroxyethyl) isocyanurate di (meth) acrylate, hydroxyethyl (meth) acrylate, hydroxypropyl (meth) acrylate, hydroxybutyl (meth) acrylate, isooctyl (meth) acrylate, isodecyl (meth) acrylate, stearyl (meth) acrylate, tetrahydrofurfuryl (meth) acrylate, phenoxyethyl (meth) acrylate or isobornyl (meth) acrylate, etc. They can be used alone or in combination of two or more. The above-mentioned acrylate compound can include epoxy (meth) acrylate compounds and / or carbamate (meth) acrylate compounds. In addition, the above-mentioned epoxy compound can include a monomer or oligomer having at least one epoxy group in the molecule. The above-mentioned epoxy group can be an alicyclic epoxy group. The carbon number of the alicyclic ring contained in the epoxy group may be 3 to 7, for example, it may be an alicyclic epoxy group containing a cyclohexane ring (cyclohexyl epoxy group). The alicyclic ring may also have a substituent. For example, the alicyclic ring may contain an alkyl substituent having 1 to 20 carbon atoms. When the carbon number of the alkyl substituent is greater than 20, it may be disadvantageous in terms of curing speed. The alkyl substituent may be a straight chain type or a branched type, and when it is a branched type, the carbon number may be 3 or more.

[0108] According to one embodiment of the present invention, in the method for manufacturing a hard coating film, the hard coating composition contains inorganic particles. According to one embodiment of the present invention, as the inorganic particles, inorganic particles with a particle size of nanometers can be used, for example, nanoparticles with a particle size of 100 nm or less, preferably 10 nm to 100 nm, and more preferably 10 nm to 50 nm can be used. In addition, as the inorganic particles, for example, silicon dioxide particles, aluminum oxide particles, titanium oxide particles, or zinc oxide particles can be used.

[0109] By including the above-mentioned inorganic particles, the hardness of the hard coating film can be further improved. According to one embodiment of the present invention, the content of the above-mentioned inorganic particles can be 10 to 60 parts by weight, preferably 20 to 50 parts by weight, relative to 100 parts by weight of the above-mentioned hard coating composition. By including the above-mentioned inorganic particles in the above-mentioned range, the hardness improvement effect of the hard coating film brought about by the addition of inorganic particles can be achieved within the range without reducing the physical properties of the hard coating composition.

[0110] According to one embodiment of the present invention, in the method for manufacturing a hard coating film, the hard coating composition includes a photoinitiator. According to one embodiment of the present invention, as the photoinitiator, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, methyl benzoylformate, α,α-dimethoxy-α-phenylacetophenone, 2-benzoyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide or bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide can be cited, but it is not limited thereto. In addition, currently commercially available products include Irgacure 184, Irgacure 500, Irgacure 651, Irgacure 369, Irgacure 907, Darocur 1173, Darocur MBF, Irgacure 819, Darocur TPO, Irgacure 907, Esacure KIP 100F, etc. These photoinitiators may be used alone or in combination of two or more different ones.

[0111] According to one embodiment of the present invention, the content of the photoinitiator can be 0.5 to 10 parts by weight, preferably 1 to 5 parts by weight, relative to 100 parts by weight of the hard coating composition. When the content of the photoinitiator is within the above range, sufficient cross-linking photopolymerization can be achieved without reducing the physical properties of the hard coating film.

[0112] In addition, in the method for producing a hard coating film of the present invention, in addition to the above-mentioned components, the hard coating composition may further contain additives commonly used in the technical field to which the present invention belongs, such as a surfactant, an anti-yellowing agent, a leveling agent, or an antifouling agent. In addition, their contents can be variously adjusted within the range that does not reduce the physical properties of the hard coating composition of the present invention, and therefore are not particularly limited.

[0113] In one or more embodiments, the thickness of the hard coating layer 800 may be 1 μm to 50 μm, preferably greater than 2 μm and less than 23 μm, and more preferably 3 μm to 20 μm. The thickness may refer to the thickness after drying. When the thickness of the hard coating layer 800 satisfies the above range, it not only has excellent bending resistance and durability, but also has advantages in being able to achieve thinness and the like.

[0114] On the other hand, in the above Figure 3 In the example, the surface protection film 700 is formed on both sides of the dimming stack 100. Figure 4 The example of forming the hard coating layer 800 on both sides of the dimming stack is used for illustration, but the invention is not necessarily limited thereto. For example, a variable transmittance optical stack according to another embodiment of the present invention may also include a dimming stack, a surface protection film formed on one side of the dimming stack, and a hard coating layer formed on the other side of the dimming stack opposite to the one side.

[0115] In addition to the above-mentioned variable transmittance optical laminate, the present invention also includes a smart window including the above-mentioned variable transmittance optical laminate. In addition, the present invention includes a car in which the above-mentioned smart window is applied to at least one of a front window, a rear window, a side window, a skylight, and an internal partition, and a window for a building including the above-mentioned smart window.

[0116] For example, in a car including the smart window of the present invention, the vehicle glass 910 (see Figure 5a ), it is also possible to bond vehicle glass 910 (see Figure 6a For example, the smart window including the above-mentioned vehicle glass can be manufactured by placing an adhesive film and the vehicle glass on both sides of the optical laminate, and then heating them for 10 to 20 minutes at a temperature of 90° C. and a vacuum state of about 1 bar using a press machine. The above-mentioned adhesive film can include an EVA film, a PVB film, etc.

[0117] In addition, a window for a building (window glass) 920 can be joined to both sides or one side of the above-mentioned variable transmittance optical laminate, and a UV adhesive can be applied to both sides of the optical laminate and then joined to the window glass, and then UV curing can be performed to produce a laminated optical laminate having a variable transmittance. Figure 5b and Figure 6b The smart window product for windows of the same structure can also be manufactured by laminating window glass on one side of the optical laminate. Figure 5c and Figure 6c Smart window products for windows of the same structure.

[0118] Implementation

[0119] The following specifically describes the embodiments of the present invention. However, the present invention is not limited to the embodiments disclosed below, but can be implemented in various different ways. The embodiments are only provided to make the disclosure of the present invention complete and to fully inform the general technicians of the technical field to which the present invention belongs of the scope of the invention. The present invention is only defined by the scope of the claims.

[0120] Manufacturing Example 1: Polarizing Plate Manufacturing

[0121] (1) Swelling treatment process

[0122] A 60 μm thick polyvinyl alcohol (PVA) film (stock film, manufactured by Kuraray Co., Ltd., trade name "Kuraray poval film VF-PE#6000", average degree of polymerization 2400, saponification degree 99.9 mol%) was continuously unwound from a stock roll and conveyed, and immersed in a swelling bath filled with pure water at 20°C for 30 seconds. In this swelling treatment step, inter-roll stretching (uniaxial longitudinal stretching) was performed by generating a difference in circumferential speed between the nip rolls. The stretching ratio was set to 2.5 times based on the stock film.

[0123] (2) Dyeing process

[0124] Next, the film passed through the nip rollers was immersed in a dyeing bath at 30°C with a ratio of pure water / potassium iodide / iodine / boric acid (mass ratio) of 100 / 2 / 0.01 / 0.3 for 120 seconds. In this dyeing treatment, inter-roll stretching (uniaxial longitudinal stretching) was performed by generating a difference in peripheral speed between the nip rollers. The stretching ratio was set to 1.1 times based on the film after the swelling treatment step.

[0125] (3) Cross-linking treatment process

[0126] Next, the film passed through the nip rollers was immersed in a first crosslinking bath of pure water / potassium iodide / boric acid (mass ratio) of 100 / 12 / 4 at 56°C for 70 seconds. Inter-roll stretching (longitudinal uniaxial stretching) was performed by causing a difference in peripheral speed between the nip rollers and the nip rollers provided between the first crosslinking bath and the second crosslinking bath. The stretching ratio was set to 1.9 times based on the film after the dyeing treatment step.

[0127] (4) Color correction process

[0128] Next, the cross-linked film was immersed in a second cross-linking bath of potassium iodide / boric acid / pure water (mass ratio) of 9 / 2.9 / 100 at 40° C. for 10 seconds.

[0129] (5) Cleaning process

[0130] Next, the membrane after the second crosslinking treatment was immersed in a cleaning bath filled with pure water at 14° C. for 5 seconds and rinsed with 5 ml 3 / h and elution temperature of 14°C for cleaning.

[0131] (6) Drying process

[0132] Next, the film after the washing treatment step was passed through a drying furnace to be heated and dried at 80° C. for 190 seconds to produce a polarizer film. The moisture content after drying was 13.6%, and the thickness of the obtained polarizer film was about 21 μm.

[0133] (7) Joining process

[0134] Next, as an adhesive, a water-based adhesive containing 5 parts by mass of polyvinyl alcohol relative to 100 parts by mass of water was manufactured. Then, on both sides of the above-mentioned polarizer film, a first triacetyl cellulose (TAC) protective film (thickness 60 μm) and a second triacetyl cellulose (TAC) protective film (thickness 40 μm) were laminated using the modulated UV adhesive. The obtained laminate was subjected to UV exposure to cure the adhesive, thereby manufacturing a polarizing plate. In addition, the thickness of the adhesive layer in the obtained polarizing plate was about 2 μm.

[0135] Manufacturing Example 2: Hard coating composition manufacturing

[0136] A hard coating composition was prepared by mixing 16.2 g of a dendrimer compound (Miyuan Specialty Chemicals, SP-1106), 14.4 g of inorganic nanoparticles (10 nm to 20 nm, silica particles: 50% by weight, solvent: methyl ethyl ketone (MEK)), 1.8 g of a polyfunctional (meth)acrylate containing an ethylene glycol group, 0.7 g of a photoinitiator (1-hydroxycyclohexyl phenyl ketone), and 2.9 g of methyl ethyl ketone.

[0137] Manufacturing Example 3: Hard Coating (HC2) Manufacturing

[0138] The hard coating composition prepared in Preparation Example 2 was applied to one side of the second triacetylcellulose (TAC) protective film (thickness 40 μm) of the polarizing plate by adjusting the thickness after drying using a Mayer bar, and dried at 80° C. for 5 minutes. The hard coating composition was then exposed to a high pressure mercury lamp at 500 mJ / cm 2 The polarizing plate with a hard coating (HC2) formed on one side was cured by applying a light of 100 μm. The thickness of the polarizing plate after the hard coating (HC2) was formed and the thickness of the polarizing plate before the hard coating (HC2) were measured using a thickness meter (MH-15M, SENDAI NIKON) and the difference between the two thicknesses was calculated. The result showed that the thickness of the hard coating (HC2) was 8 μm.

[0139] Manufacturing Example 4: Surface Protection Film (PF) Manufacturing

[0140] A 20 μm adhesive layer and a 38 μm PET film were laminated on the opposite side of the hard coat layer (HC2) of the polarizing plate prepared in Production Example 3 using a surface protection film (LDM-EPCB, LGC) to produce a polarizing plate with a surface protection film.

[0141] Manufacturing Example 5: Transparent Conductive Layer (ITO / IML) Manufacturing

[0142] The polarizing plate with a surface protection film attached in Manufacturing Example 4 is placed, and after applying a 450W DC power supply to start the sputtering gun, the plasma is directed to the ITO (10wt% Sn doped (doped) In2O3) target to form a transparent conductive layer (90nm) on one side of the hard coating (HC2), thereby respectively producing a first conductive laminate and a second conductive laminate having a laminated structure of a surface protection film / polarizing plate / hard coating / transparent conductive layer. The ion gun is started with a 50W DC power to perform ion treatment on the transparent conductive layer formed above. At this time, the pressure is maintained at 3mTorr at room temperature, and argon and oxygen are supplied at 30sccm and 1sccm respectively for manufacturing. At this time, regarding the ITO performance, the ITO thickness is measured using FT-SEM, and the ITO surface resistance (Ω / □) is measured using a four-point probe.

[0143] Manufacturing Example 6: Oriented Film Manufacturing

[0144] An alignment liquid was applied to the transparent conductive layer (ITO / IML) surface of the first conductive laminate and the second conductive laminate prepared in the above manufacturing example 5 and dried (80°C / 2 minutes). Then, UV was irradiated on the dried alignment liquid to form an alignment film, thereby preparing an upper side laminate and a lower side laminate having a laminate structure of a surface protection film / polarizing plate / hard coating layer / transparent conductive layer / alignment film.

[0145] Manufacturing Example 7: Spherical Spacer Dispersion

[0146] The mixed solvent was prepared by mixing 0.03 g of a spherical spacer (SEKISUI SP series) with 100 ml of IPA. Then, the lower side laminate of the above-mentioned manufacturing example 6 was placed in a spacer dispenser (SDSS-KHU02, Shinto Giken Co., Ltd.), and the mixed solvent prepared above was spread at 110° C. and dried for 20 minutes, thereby forming a spherical spacer on the alignment film of the lower side laminate of the manufacturing example 6.

[0147] Manufacturing Example 8: Manufacturing of a variable transmittance optical laminate

[0148] On the transparent conductive layer (ITO / IML) surface of the lower side stack formed with spherical spacers according to Manufacturing Example 7, a frame sealant dispenser (SHOTmini 200Ωx, MUSASHI) and a sharp needle (SPN-0.25-12.7L) were used to apply frame sealant (UVF-006, 70,000 mPa·s, Sekisui Co., Ltd.) at a discharge pressure of 200 mPa according to the product size drawing, and liquid crystal was injected into the orientation film by One Drop Filling (ODF). Then, in the state where the polarization axes of the polarizing plates in the upper side stack of Manufacturing Example 6 and the above-mentioned lower side stack were arranged parallel to each other at 0° or 90°, 3Kg / cm 2 The two layers are bonded by pressure, thereby manufacturing a variable transmittance optical stack for a smart window.

[0149] Examples and Comparative Examples

[0150] Example 1

[0151] The variable transmittance optical layered body of Example 1 was produced according to the above-mentioned Production Examples 1 to 8.

[0152] Example 2

[0153] A variable transmittance optical laminate of Example 2 was produced in the same manner as in Example 1 except that a surface protection film (AY-638 from Fujimori Co., Ltd.) was used in Production Example 4.

[0154] Example 3

[0155] The variable transmittance optical layered body of Example 3 was produced in the same manner as in Example 1, except that a hard coat layer (HC1) was produced in place of the surface protection film in Production Example 4. The hard coat layer (HC1) was produced in the same manner as in Production Example 3 using a Meyer bar to a thickness of 3 μm.

[0156] Example 4

[0157] The variable transmittance optical layered body of Example 4 was produced in the same manner as in Example 1 except that a hard coat layer (HC1) was produced instead of the surface protection film in Production Example 4. The hard coat layer (HC1) was produced in the same manner as in Production Example 3 using a Meyer bar with a thickness of 20 μm.

[0158] Comparative Example 1

[0159] A variable transmittance optical laminate of Comparative Example 1 was produced in the same manner as in Example 1 except that the surface protection film (LDM-EPHC, LGC Corporation) was used in Production Example 4.

[0160] Comparative Example 2

[0161] A variable transmittance optical laminate of Comparative Example 2 was produced in the same manner as in Example 1, except that a surface protection film (AS3-501 from Fujimori Co., Ltd.) was used in Production Example 4.

[0162] Comparative Example 3

[0163] The variable transmittance optical layered body of Comparative Example 3 was produced in the same manner as in Example 1, except that a hard coat layer (HC1) was produced in place of the surface protection film in Production Example 4. The hard coat layer (HC1) was produced in the same manner as in Production Example 3 using a Meyer bar with a thickness of 2 μm.

[0164] Comparative Example 4

[0165] The variable transmittance optical layered body of Comparative Example 4 was produced in the same manner as in Example 1, except that a hard coat layer (HC1) was produced in place of the surface protection film in Production Example 4. The hard coat layer (HC1) was produced in the same manner as in Production Example 3 using a Meyer bar with a thickness of 23 μm.

[0166] Experimental example

[0167] (1) Peel force evaluation

[0168] The variable transmittance optical laminates of Examples 1 and 2 and Comparative Examples 1 and 2 were cut into 25 mm*250 mm sizes using a super cutter, and then bonded to an adhesive glass plate to prepare test pieces. After the prepared test pieces were fixed to a universal testing machine, the 180° peeling force (N / 25 mm) between the dimming laminate and the surface protective film was measured at a speed of 300 mm / min. The measurement results are shown in Tables 1 and 2 below.

[0169] (2) Appearance reliability evaluation

[0170] For the optical laminates of Examples 1 and 2 and Comparative Examples 1 and 2, the surface protective films were peeled off from both sides of the optical laminate of 38" size (800x500mm) according to the method described in Korean Patent Publication No. 10-2013-0060879 to confirm whether the frame sealant was cracked and bubbles occurred. The evaluation results are shown in Tables 1 and 2 below.

[0171] <Evaluation Criteria>

[0172] ○: Good evaluation results (no cracks in the sealant and no bubbles in the liquid crystal layer)

[0173] X: Poor evaluation result (bubbles in the adhesive layer during ITO evaporation or cracks or bubbles in the sealant during peeling)

[0174] (3) Measurement of the thickness of the hard coating (HC1)

[0175] For the optical laminates of Examples 3 and 4 and Comparative Examples 3 and 4, a thickness gauge (MH-15M, Sendai Nikon Corporation) was used to measure the thickness of the polarizing plate after the hard coating layer (HC1) was formed and the thickness of the polarizing plate before the hard coating layer (HC1) was formed and the difference between the two thicknesses was calculated, thereby calculating the thickness of the hard coating layer (HC1). The measurement results are shown in the following Tables 1 and 2.

[0176] (4) Surface pencil hardness evaluation

[0177] For the optical laminates of Examples 3 and 4 and Comparative Examples 3 and 4, the surface pencil hardness of the hard coating surface was measured by applying a load of 500 g using a pencil hardness tester (Sukbo Science Co., Ltd., South Korea). A Mitsubishi product was used for each pencil hardness, and scratches were confirmed with the naked eye after heat treatment at 100°C for 10 minutes. The evaluation results are shown in the following Tables 1 and 2.

[0178] (5) Steel wool test

[0179] For the optical laminates of Examples 3 and 4 and Comparative Examples 3 and 4, the wear resistance of the hard coating of the optical laminate was tested by using a steel wool tester (WT-LCM100, Protech Co., Ltd., Korea) at 1 kg / (2 cm x 2 cm) and reciprocating 10 times at a speed of 100 mm / sec. The steel wool used was #0000. The evaluation results are shown in the following Tables 1 and 2.

[0180] <Evaluation Criteria>

[0181] ○: 0 scratches and no discoloration

[0182] △: 1 to 10 scratches and no discoloration

[0183] X: There are more than 10 scratches and discoloration is confirmed (by naked eye)

[0184] (6) Reliability mandrel evaluation

[0185] For the optical laminates of Examples 3 and 4 and Comparative Examples 3 and 4, in order to evaluate the bending characteristics and crack resistance by a round-type bending tester (Lab-Q D605, CKSI), a sample specimen with a size of 100 x 100 mm and upper / lower plates bonded was placed in a manner such that the lower plate surface of the polarizing plate was in contact with an iron rod with a diameter of 32 mm, and in a folded state, a load of 1 kg was applied to the outside of the folded portion and placed in a 90° C. oven for 2 hours, and then the sample was placed at room temperature, and the folded area was observed to confirm whether cracks were generated. The evaluation results are shown in Tables 1 and 2 below.

[0186] <Evaluation Criteria>

[0187] ○: 0 cracks

[0188] X: More than one crack

[0189] [Table 1]

[0190] Example 1 Example 2 Example 3 Example 4 Peel force (N / 25mm) 1.0 2.4 - - Appearance reliability evaluation ○ ○ - - Hard coating (HC1) thickness - - 3 20 Surface pencil hardness - - HB 6H Steel Wool Test - - ○ ○ Reliability mandrel evaluation - - ○ ○

[0191] [Table 2]

[0192] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Peel force 0.7 2.6 - - Appearance reliability evaluation X X - - Hard coating (HC1) thickness - - 2 23 Surface pencil hardness - - B 7H Steel Wool Test - - X X Reliability mandrel evaluation - - ○ X

[0193] Referring to Tables 1 and 2 above, in the case of Examples 1 and 2, where the peeling force of the surface protective film is 1.0N / 25mm to 2.4N / 25mm, respectively, it can be seen that in the appearance reliability evaluation results, no cracking of the sealant and bubbles in the liquid crystal layer occurred after peeling off the surface protective film. On the contrary, in the case of Comparative Examples 1 and 2, where the peeling force of the surface protective film is 0.7N / 25mm and 2.6N / 25mm, respectively, and deviates from 1.0N / 25mm to 2.4N / 25mm, it can be seen that bubbles are generated at the attachment interface of the surface protective film during ITO evaporation or that the sealant cracks or bubbles are generated during peeling.

[0194] On the other hand, in the case of Examples 3 and 4, in which the surface pencil hardness of the hard coating layer was HB to 6H, it was found that the wear resistance of the hard coating layer was excellent in the steel wool test results, and the bending characteristics were excellent in the reliability mandrel evaluation without cracks. On the other hand, in the case of Comparative Examples 3 and 4, in which the surface pencil hardness of the hard coating layer was B and 7H, respectively, which was out of the range of HB to 6H, it was found that the steel wool test results and the reliability mandrel evaluation results were inferior to those of the Examples.

[0195] It can be seen from this that an optical laminate can be provided in which the peeling force of the surface protective film included in the optical laminate is 1.0N / 25mm~2.4N / 25mm, and when the surface protective film is peeled off, the frame sealing glue can be prevented from being damaged and bubbles can be prevented from entering the liquid crystal. Even if the optical laminate does not have the above-mentioned surface protective film but includes a hard coating layer with a surface pencil hardness of HB~6H, the optical laminate has excellent wear resistance and bending properties and can protect the polarizing plate from the influence of the external environment.

[0196] Industrial Applicability

[0197] According to an embodiment of the optical laminate of the present invention, since the peeling force of the surface protection film is optimized, it is possible to prevent the frame sealant from being damaged and bubbles from entering the liquid crystal when the surface protection film is peeled off.

Claims

1. A variable transmittance optical stack, comprising a dimming stack, wherein the dimming stack comprises: a first polarizing plate; A first transparent conductive layer formed on one surface of the first polarizing plate; a second polarizing plate, which is opposite to the first polarizing plate; A second transparent conductive layer formed on one side of the second polarizing plate and opposite to the first transparent conductive layer; as well as a liquid crystal layer disposed between the first transparent conductive layer and the second transparent conductive layer, The dimming stack has at least one of a surface protection film and a hard coating layer on one or both surfaces thereof, At least one of the first transparent conductive layer and the second transparent conductive layer is formed to be in direct contact with one of the first polarizing plate and the second polarizing plate. The peeling force of the surface protection film is 1.0N / 25mm to 2.4N / 25mm. The surface pencil hardness of the hard coating layer is HB to 6H. 2 . The variable transmittance optical stack according to claim 1 , wherein the surface protection film comprises a base film and an adhesive layer formed on the base film, and is stacked on the light-adjusting stack using the adhesive layer as a medium. 3 . The variable transmittance optical laminate according to claim 2 , wherein the substrate film comprises at least one selected from the group consisting of polyolefin films, polyester films, acrylic films, styrene films, amide films, polyvinyl chloride films, polyvinylidene chloride films, and polycarbonate films. 4 . The variable transmittance optical laminate according to claim 2 , wherein the base film has a thickness of 10 μm to 300 μm. 5 . The variable transmittance optical laminate according to claim 2 , wherein the adhesive layer has a thickness of 1 μm to 30 μm. 6 . The variable transmittance optical laminate according to claim 1 , wherein when the surface protection film is peeled off from the light-adjusting laminate, the liquid crystal layer does not have cracks or bubbles. 7 . The variable transmittance optical stack according to claim 1 , further comprising surface protection films on both surfaces of the light-adjusting stack. 8 . The variable transmittance optical stack according to claim 1 , further comprising a hard coating layer on both surfaces of the light adjusting stack. 9 . The variable transmittance optical stack according to claim 1 , further comprising a hard coating layer on one surface of the light adjusting stack and a surface protection film on the other surface of the light adjusting stack opposite to the one surface. 10 . The variable transmittance optical layered body according to claim 1 , wherein the hard coat layer comprises at least one selected from the group consisting of acrylate compounds and epoxy compounds. 11 . The variable transmittance optical layered body according to claim 1 , wherein the hard coat layer has a thickness of 1 μm to 50 μm.

12. The variable transmittance optical stack according to claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer comprises one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires. 13 . The variable transmittance optical laminate according to claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate comprises one or more functional layers selected from the group consisting of a protective layer, a phase difference adjusting layer, and a refractive index adjusting layer. 14 . The variable transmittance optical laminate according to claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate has a thickness of 30 μm to 200 μm. 15 . The variable transmittance optical stack according to claim 1 , wherein the liquid crystal layer includes one or more spacers selected from the group consisting of spherical spacers and columnar spacers. 16 . The variable transmittance optical stack according to claim 15 , wherein the height of the spacer is 1 μm to 10 μm. 17 . The variable transmittance optical stack according to claim 15 , wherein the area occupied by the spacer in the liquid crystal layer is 0.01% to 10% of the area of ​​the liquid crystal layer. 18 . The variable transmittance optical laminate according to claim 1 , further comprising alignment films on both surfaces of the liquid crystal layer. 19 . A smart window comprising the variable transmittance optical laminate according to claim 1 .

20. A vehicle comprising the smart window according to claim 19.

21. An automobile, wherein the smart window according to claim 19 is applied to at least one of a front window, a rear window, a side window, a skylight, and an interior partition.

22. A wearable device comprising the smart window according to claim 19.

23. A building window, comprising the smart window according to claim 19.

Citation Information

Patent Citations

  • Surface protecting film and laminate comprising thesame

    KR1020010101097A

  • Apparatus and Method for peeling protection film

    KR1020130060879A